Sustaining the skill base of technical and further education institutes : TAFE managers' perspectives - Clayton, Berwyn [Verfasser]; Fisher, Thea [Verfasser]; Hughes, Elvie [Verfasser] (NCVER, 2005)
"The demographic changes in Australia's labour market present challenges for technical and further education (TAFE) institutes. Within TAFE institutes, in which the teaching workforce is older than the overall national labour force, the imminent departure of many teachers endangers its prime asset - its skill and knowledge base. This report examines the approaches managers and leaders in 16 TAFE institutes have undertaken to sustain, develop and renew their workforce and build their organisation's knowledge. It finds that TAFE managers now recognise that maintaining and developing their organisation's skill base is imperative, but that finding approaches to sustain TAFE in the longer term requires more attention." (BIBB-Doku)
Keywords: P 3.2 Lehrpersonal; S 5.2 Wissensmanagement; I 2.3.5 Australien, Ozeanien; Bildungsträger; Bildungspersonal; Technische Bildung; Weiterbildung; Wissensmanagement; Erfahrungswissen; Australien